Investigating Relationships Between Learning Environment Perceptions, Motivation and Self-Regulation for Female Science Students in Abu Dhabi, United Arab Emirates - Aldridge, Jill; Rowntree, Kate (2021)
The global lack of student motivation towards learning science and gender imbalance in STEM careers provided the impetus for this study, which had two key aims: (1) to examine the influence of female students’ perceptions of the psychosocial learning environment on their motivation towards and self-regulation in science learning,; and (2) to investigate the influence of their reported motivation on their self-regulation of effort. Data were collected from 338 female students in grades 6 to 9 science classes across 16 government schools in Abu Dhabi, in the United Arab Emirates. Structural equation modelling was used to explore the hypothesised relationships, which indicated that there were statistically significant relationships between learning environment perceptions, motivation and self-regulation. The results provide exigent information to both teachers, policy-makers and researchers with regard to the influences of the psychosocial learning environment on female students’ motivation towards science, as well as the influence of motivation towards science on their self-regulatory behaviour within science classroom settings.